1975
DOI: 10.1088/0031-9155/20/4/007
|View full text |Cite
|
Sign up to set email alerts
|

In vivo electron spin resonance in rats

Abstract: In vivo ESR studies have been made on Wistar and Sprague-Dawley rats using travelling wave helices implanted in the left lobe of the liver. Tissue regenerates completely around the Teflon-enclosed turns of the coil and histological studies have shown that it is composed of liver cells and connective tissue. Electron spin resonance studies of this tissue in vitro reported by Commoner and Ternberg in 1961 have demonstrated that it exhibits the 'tissue radical' signal. The implanted coils have detected, in vivo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…The contemporary pioneering experiment was reported by Piette and colleagues in 1975 at the University of Hawaii [30]. They implanted a helix resonator in the liver of a rat and administered high doses of the piperidine nitroxide TEMPOL (or 1-hydroxy-2,2,6,6-tetramethylpiperidine-N-oxyl).…”
Section: In-vivo Studies Of Small Animals: Early Attemptsmentioning
confidence: 99%
See 2 more Smart Citations
“…The contemporary pioneering experiment was reported by Piette and colleagues in 1975 at the University of Hawaii [30]. They implanted a helix resonator in the liver of a rat and administered high doses of the piperidine nitroxide TEMPOL (or 1-hydroxy-2,2,6,6-tetramethylpiperidine-N-oxyl).…”
Section: In-vivo Studies Of Small Animals: Early Attemptsmentioning
confidence: 99%
“…This is basically incorporating the compounds, aminoxyl (aka nitroxide) radicals that are used in spin labeling, but targeting them (if possible) to specific regions of the body, organs, etc. In fact, the work from the Piette group was one of the earliest examples [30]. We initially worked on the same X-band system after Piette trying to measure EPR at the carotid artery in a rat, but realized quickly that the microwave heating at 9.5 GHz was a real issue [unpublished results].…”
Section: Incorporation Of Aminoxyl (Aka Nitroxide) Radicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Probably the most controversial concern in this regard relates to the vast number of ESR measurements made on excised tissue or cell suspensions. In order to answer this question, Feldman et al 4 reported one of the first in vivo ESR studies on a modified X-band ESR instrument employing a traveling wave helix structure in place of the standard microwave cavity. They reported the first in vivo ESR study in the liver of intact rats.…”
Section: Introduction: History Of In Vivo Epr or Esrmentioning
confidence: 99%
“…According to Piette and coworkers, 4 the ideal in vivo ESR spectrometer was one in which a live animal could be directly accommodated, which was virtually impossible with commercial X-band microwave spectrometers operating at 9.4 GHz. The instrumental requirements for in vivo animal studies are two-fold: (1) a resonant device with dimensions suitable to fit the body of small animals; and (2) a choice of an operating frequency that does not produce dielectric heating, like a microwave oven.…”
Section: Introduction: History Of In Vivo Epr or Esrmentioning
confidence: 99%